Selection of Pof-Saccharomyces eubayanus Variants for the Construction of S. cerevisiae × S. eubayanus Hybrids With Reduced 4-Vinyl Guaiacol Formation - Diderich, Jasper A.; Weening, Susan M.; van den Broek, Marcel; Pronk, Jack T.; Daran, Jean-Marc G. (Frontiers in Microbiology, 2018)
Saccharomyces pastorianus is an interspecies hybrid between S. cerevisiae and S. eubayanus. The identification of the parental species of S. pastorianus enabled the de novo reconstruction of hybrids that could potentially combine a wide array of phenotypic traits. Lager yeasts are characterised by their inability to decarboxylate ferulic acid present in wort, a phenotype also known as Pof- (phenolic off-flavour). However, all known S. eubayanus strains characterized so far produce clove-like aroma specific of 4-vinyl guaiacol, a decarboxylated form of ferulic acid. This study explored a non-GMO approach to construct Pof- S. eubayanus variants derived from the parental strain S. eubayanus CBS 12357. To rapidly screen a population of UV-mutagenized cells two complementary assays were developed. The first assay was based on the difference of light absorption spectra of ferulic acid and 4-vinyl guaiacol, while the second was based on the difference of sensitivity of Pof- and Pof+ strains to cinnamic acid. The S. eubayanus variant HTSE042 was selected and was confirmed not to produce 4-vinyl guaiacol. Whole genome sequencing revealed that this variant lost the subtelomeric region of the CHRXIII right arm that carried the two clustered genes SePAD1- SeFDC1 whose deletion in a naïve S. eubayanus strain (CBS 12357/FM1318) resulted in an identical phenotype. Subsequently, the Pof- variant was crossed with a Pof- S. cerevisiae partner. The resulting hybrid was not able to convert ferulic acid demonstrating the undisputable value of the mutant HTSE042 to eventually construct S. cerevisiae x S. eubayanus hybrids with phenotypic characteristics of S. pastorianus.